Hubungan Pengelolaan Emosi Siswa dengan Interaksi Sosial di Kelas IV SDN Cipinang Cempedak 07 - Maulidya, Aisyah; Petrus Suhendro; Adi Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Emotional management skills play an important role in forming positive social interactions and supporting the development of students' character from an early age. This study aims to examines the relationship between emotional management and social interactions of fourth-grade students at SDN Cipinang Cempedak 07. With a quantitative approach and correlational method, data were obtained from 63 students through questionnaires and observations. The results of the analysis showed a very strong and significant correlation (r = 0.818; p < 0.001), indicating that the ability to manage emotions is closely related to the quality of students' social interactions, so it is important to be integrated into learning in elementary schools